The Effectiveness of Group CBT in Reducing Symptoms of Generalized Anxiety Disorder in Adult Pre-operative Patients - Muhammad Alghifari Budiman; Diki Armansyah Damanik (Journal of Applied Psychology and Health Studies, 2025)
Generalized Anxiety Disorder (GAD) is a common anxiety disorder characterized by excessive and uncontrollable worry in daily life. This condition is very common among adult patients who are about to undergo surgery. Anxiety that arises before surgery, or preoperative anxiety, can trigger excessive physiological responses such as increased heart rate, blood pressure, and hormonal stress, which can potentially negatively affect surgical outcomes and the postoperative recovery process. Therefore, effective interventions to reduce this anxiety are an important aspect of healthcare, especially in relation to the patient's mental preparedness before surgical procedures. One widely used and proven effective psychological intervention method is Cognitive Behavioral Therapy (CBT), a therapeutic approach that focuses on changing maladaptive thought patterns and behaviors underlying anxiety disorders. CBT in a group format not only provides therapeutic benefits but also offers the advantages of resource efficiency and social support among participants, making it highly suitable for implementation in hospital and healthcare settings. Objective: This study aims to analyze the effectiveness of group CBT in reducing anxiety symptoms in adult preoperative patients and to explore the underlying mechanisms of the intervention's success. Through a narrative review of various studies, it is hoped that the extent to which group CBT has a positive effect on patients' psychological readiness before surgery can be determined. Methods: This study used a narrative review method by collecting and evaluating relevant current literature in the PubMed and Google Scholar databases. The main focus is on studies that use the Randomized Controlled Trial (RCT) method to assess the effectiveness of group CBT in a population of adult preoperative patients. In this study, six RCT journals with a sample size of 70 to 100 participants per study were critically analyzed to draw comprehensive conclusions. Method: The study used a narrative review method by collecting and evaluating relevant current literature in the PubMed and Google Scholar databases. The main focus was on studies that used the Randomized Controlled Trial (RCT) method to assess the effectiveness of group CBT in adult preoperative patients. In this review, six RCT journals with a sample size of 70 to 100 participants per study were critically analyzed to draw comprehensive conclusions. Results: Findings from the studies reviewed showed that the application of CBT in a group format significantly reduced anxiety levels in preoperative patients compared to control groups that did not receive intervention or only received standard care. In addition, several studies indicate that the effectiveness of group CBT is almost comparable to individual CBT, providing a more practical and resource-efficient treatment alternative. The combination of CBT with pharmacotherapy was also found to be superior in reducing anxiety compared to using pharmacology alone, confirming the benefits of a multimodal approach in the treatment of preoperative GAD. Conclusion: CBT in a group format has been proven to be an effective intervention for reducing preoperative anxiety, primarily through cognitive restructuring, i.e., changing negative thought patterns to more realistic and adaptive ones, as well as social support gained from group interaction. Therefore, the implementation of group CBT is highly recommended in healthcare services as a strategy to enhance patients' mental preparedness, improve perioperative experiences, and enhance post-operative clinical outcomes.